Effects of a patient decision aid for nonmetastatic prostate cancer established in routine care: the randomized controlled EvEnt-PCA trial - Huber, Johannes; Karschuck, Philipp; Koch, Rainer; Ihrig, Andreas; Krones, Tanja; Neisius, Andreas; Ahn, Sven von; Klopf, Christian Peter; Weikert, Steffen; Siebels, Michael; Haseke, Nicolas Sven; Weißflog, Christian; et al. (European urology focus, 2025)
Background and objective: Since 2016, >21 000 patients with prostate cancer (PC) used our personalized online decision aid in routine care in Germany. We analyzed the effects of this online decision aid for men with nonmetastatic PC in a randomized controlled trial. Methods: In the randomized controlled EvEnt-PCA trial, 116 centers performed 1:1 allocation of 1115 patients with nonmetastatic PC to use an online decision aid (intervention = I) or a printed brochure (control = C). The primary outcome was treatment decision after 14 mo. The secondary endpoints were knowledge, acceptance, decisional conflict, physician-patient communication, anxiety and depression, decision regret, and quality of life. Key findings and limitations: With complete data from 1000 patients, there was no difference between the two groups in terms of primary or secondary endpoints. In the intervention group, consultation time was shorter (I: 61 min vs C: 70 min, p = 0.02), and more patients provided a summary of their preparation (I: 76% vs C: 56%, p < 0.001). Life expectancy (I: 53% vs C: 47%, p = 0.03), radiotherapy (I: 90% vs C: 84%, p = 0.005), rehabilitation (I: 69% vs C: 62%, p = 0.02), and psycho-oncology (I: 21% vs C: 16%, p = 0.07) were discussed more frequently in the intervention group. Additionally, more counseling sessions with general practitioners (I: 43% vs C: 35%, p = 0.01) and radiotherapists (I: 24% vs C: 18%, p = 0.03) were held in the intervention group. Conclusions and clinical implications: The use of the online decision aid was associated with structural improvements, for example, significantly shorter doctor-patient consultation time. Our findings suggest stronger guideline adherence in the counseling process and promotion of health literacy. Successful implementation of our online decision aid in routine care can provide an example for solving this key obstacle for shared decision-making.
Gesehen am 18.02.2026
Online verfügbar: 9. September 2025, Artikelversion: 10. Dezember 2025